Ballistic tracks in graphene nanoribbons - Johannes Aprojanz (Nature Portfolio, 2018)
Electronic highways were realized by means of epitaxially grown graphene nanoribbons on SiC substrates. Here, the authors use spatially-resolved two-point probe and conductive AFM measurements, supplemented by tight-binding calculations, to image the one-dimensional ballistic transport channels.